Remote patient monitoring sustains reductions of hemoglobin A1c in underserved patients to 12 months. Issue 3 (June 2021) - Kirkland, Elizabeth B.; Marsden, Justin; Zhang, Jingwen; Schumann, Samuel O.; Bian, John; Mauldin, Patrick; Moran, William P.
Highlights: Remote patient monitoring (RPM) is an effective, accessible tool for diabetes care. Rural and underserved populations achieved significant improvements in HbA1c. HbA1c reductions were sustained at 6 and 12 months of RPM program participation. Patients of varying demographics and clinic types achieved similar clinical benefit. Abstract: Aims: We sought to determine whether underserved patients enrolled in a statewide remote patient monitoring (RPM) program for diabetes achieve sustained improvements in hemoglobin A1c at 6 and 12 months and whether those improvements are affected by demographic and clinical variables. Methods: Demographic and clinical variables were obtained at baseline, 6 months and 12 months. Baseline HbA1c values were compared with those obtained at 6 and 12 months via paired t-tests. A multivariable regression model was developed to identify patient-level variables associated with HbA1c change at 12 months. Results: HbA1c values were obtained for 302 participants at 6 months and 125 participants at 12 months. Compared to baseline, HbA1c values were 1.8% (19 mmol/mol) lower at 6 months (p < 0.01) and 1.3% (14 mmol/mol) lower at 12 months (p < 0.01). Reductions at 12 months were consistent across clinical settings. A regression model for change in HbA1c showed no statistically significant difference for patient age, sex, race, household income, insurance, or clinic type. Conclusions: Patients enrolled in RPM had improved diabetes control at 6 and 12 months. Neither clinic type nor sociodemographic variables significantly altered the likelihood that patients would benefit from this type of technology. These results suggest the promise of RPM for delivering care to underserved populations.